FRI0506 Hla profiles and their associations with disease phenotypes in a canadian psoriatic arthritis (PSA) cohort. (15th June 2017) - Khraishi, M; Molta, C; Khraishi, Z; Lewis, AM
Abstract : Background: PSA is a chronic disease with known genetic predisposition that affects 0.3% to 1% of the general population.Certain HLA allelles were reported to be more predominant in PSA and to be associated with certain manifestations. Objectives: To determine HLA alleles prevalence in PSA patients and their association with clinical features and the severity of PSA in these patients Methods: Two cohorts of early (established PSA)were followed prospectively.Clinical and laboratory data were collected at 6 months intervals, included PASI scores, nail involvement, joint counts, patient reported outcomes, comorbidities, inflammatory parameters and HLA Class I typing. Statistics utilized IBM SPSS v.23. Frequencies, means, medians and 2-tailed Pearson correlation were calculated.As the majority of our patients have Irish ancestry, we utilized HLA prevalence from an Irish population based data Results: The cohorts included 265 patients. Of those, one hundred thirty five patients had their HLA analysis done. Fifty one percent of the patients were male, the mean age at onset of PSA 43.07 (19–76) years. Mean age of PSO diagnosis was 33.47 years. Sixty four percent had polyarticular involvement at base line and 17% had documented axial involvement. Forty two haplotypes were reported in our cohort of those: HLA B27 was present in 33% of the patients (as compared to 6.77% in an Irish control population). HLAA1 was present in 31%, B8 in 21%, B57 in 6.6%B44 in 24.5%, B51 in 10%B58 in 5.6%, HLA B62 in 7%, HLA Bw4 in 43.6%and Bw6 in 46.5%. The following associations were found to be significant: HLAB49 was negatively associated with age of onset of PSA with a Pearson correlation of -0.610 (P 0.007), also, HLA A23 had a correlation of -0.232 (P 0.016) B44 was associated with increased total number of comorbidities, Pearson correlation was 0.332 (P 0.0001) HLA B22 was associated with more severe PASI score with a correlation of 0.488 (P 0.000) Of note that the only case in the cohort with Crohn's disease had HLA B12 which was previously reported in spondylitis 135 patients were studied, 51% were male. The mean age of PSA onset was 43.07 yearsand 33.4 for PSO. 64% had polyarticular disease while 17% had axial involvement. 42 alleles were studied, of those, HLA B27 was present in 33% of patients (vs.6.77% controls) HLAA1 in 31%, B8 in 21%, B57 in 6.6%, B44 in 24.5%, B51 in 10%, B58 in 5.6%, HLA B62 in 7%, HLA Bw4 in43.6%, Bw6 in 46.5%. The following associations were significant: HLAB49& HLA A23 were associated with age of onset of PSA (correlation of -0.610 (P.007) and -0.232 (P.016) respectively. HLA B44 was associated with increased number of comorbidities (correlation 0.332 (P.0001), HLA B22 was associated with severe PASI score (correlation of 0.488 (P.000).The only case in our cohort with Crohn's disease had HLA B12 (previously reported in spondylitis) Conclusions: The majority of patients had polyarticular involvement.HLABw6 and HLA Bw4 were the most frequent allelles. We found high percentage of patients with HLAB27, HLAA1 vs controls.HLA B27 prevalence was higher in patients with axial involvement but it did not reach significance in our cohort.HLA B44 was strongly associated with increased comorbidities (previous reports suggested protective effect of this allelle).HLA B22 was associated with more severe PASI scores. Disclosure of Interest: None declared